Alameda County State College Summer School 1962 - Alameda County State College:::::: (Alameda County State College; California State Printing Office, 1962)
A catalog of courses offered by State College for Alameda County for the summer quarter in 1962. Includes academic calendar, names of faculty and administrators, schedule of classes, and descriptions of courses offered.